2009
DOI: 10.1111/j.1468-3083.2008.02926.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary syphilis mimicking pemphigus vulgaris

Abstract: References1 Rasktar G, Okagaki T, Twiggs LB, Clark BA. Early invasive and in situ warty carcinoma of the vulva. clinical, histologic, and electron microscopic study with particular reference to viral association. Am J Obstet Gynecol 1982; 143: 814-820. 2 Aroni K, Lazaris AC, Ioakim-Liossi A, Paraskevakou H, Davaris PS. Histological diagnosis of cutaneous 'warty' carcinoma on a pre-existing HPV lesion. Acta Derm Venereol 2000; 80: 294-296. 3 Cho NH, Joo HJ, Ahn HJ, Jung WH, Lee KG. Detection of human papillomav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…In contrast to published data, mucosal patches are detected in only the 16% of patients and any evidence of leukoplakia‐like lesions. Interestingly, case 2 affected by syphilis in secondary stage mimicking a blistering mucositis is never described in the current literature up to the paper by Mignogna et al (). Another interesting data are the necrosis of the dorsum of the tongue in patient 11 with tertiary disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to published data, mucosal patches are detected in only the 16% of patients and any evidence of leukoplakia‐like lesions. Interestingly, case 2 affected by syphilis in secondary stage mimicking a blistering mucositis is never described in the current literature up to the paper by Mignogna et al (). Another interesting data are the necrosis of the dorsum of the tongue in patient 11 with tertiary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hair loss can also occur (moth-eaten alopecia/alopecia syphilitica), typically affecting the scalp, but also the eyebrows or total body hair loss. Secondary syphilis has been termed the “great masquerader”, because its skin lesions show such diverse clinical and/or histologic morphologies, mimicking alopecia areata (130), bullous pemphigoid (131), cutaneous lymphoid hyperplasia (pseudolymphoma) (132–135), erythema multiforme (126, 136), granuloma annulare (43, 128, 137, 138), histiocytoma (34), leprosy (128, 139, 140), lichen planus (34, 126, 135, 141, 142), lupus erythematosus (43, 128, 143), mycosis fungoides (126, 144146), pemphigus vulgaris (147), pityriasis lichenoides et varioliformis acuta (PLEVA) (34, 126, 135), pruritic (eczematous) dermatoses (126, 128, 148), psoriasis (34, 128, 149, 150), pustular psoriasis (34, 128), sarcoidosis (34, 135, 151–155), small vessel vasculitis (156), suppurative folliculitis (157), superficial thrombophlebitis (158), Sweet’s syndrome (128, 159), tinea imbricata and erythema annulare centrifugum (34, 160), and urticaria (104). Ulcerative nodular presentations are rare and can occur secondary to follicular pustules (157, 161), or an obliterative endarteritis, known as lues maligna (162, 163).…”
Section: The Pathology Of Human Syphilismentioning
confidence: 99%
“…Differently, Hamlyn et al [9] reported a case series of three patients in whom secondary syphilis presented solely as a tonsillitis. A comprehensive review of the literature shows that oral lesions have been described as solitary or multiple ulcerations [7, 14, 18, 23, 32, 33], as erosions [10, 14], as a bullous-erosive lesion resembling pemphigus vulgaris [34], as macular, papular, and nodular lesions [3, 14, 18], as condylomata lata [6], as leukoplakia-like [35, 36], as oral hairy leukoplakia-like [8, 18] lesions, and as painless nodules on the tongue [37]. …”
Section: Discussionmentioning
confidence: 99%